Serotonin markers show altered transcription levels in an experimental pig model of mitral regurgitation. Issue 2 (February 2015) - Cremer, S.E.; Zois, N.E.; Moesgaard, S.G.; Ravn, N.; Cirera, S.; Honge, J.L.; Smerup, M.H.; Hasenkam, J.M.; Sloth, E.; Leifsson, P.S.; Falk, T.; Oyama, M.A.; et al.
Highlights The effects of mitral regurgitation (MR) on selected serotonin 5-hydroxytryptamine (5-HT) markers were evaluated in pigs. Haemodynamic changes associated with MR resulted in increased 5-HT2BR (R) and decreased serotonin re-uptake transporter (SERT) gene expression in mitral valves. MR may contribute to altered valvular 5-HT signalling and pathological valvular changes.